Perspectives on Maimonides : philosophical and historical studies - Kraemer, Joel L.; Berman, Lawrence V. (Lawrence Victor); Blau, Joshua, 1919-2020 (Littman library of Jewish civilization (Series), 2008)
This is a text on the philosophy and legal views of Moses Maimonides (1138-1204) and the historical context in which he worked. The philosophical section examines Maimonides' ethical doctrine; his paradoxical life-style; his 'Guide of the Perplexed'; his attitude to mysticism; his use of language; and his theory of astronomy. The legal section deals with law and medicine, the relation of Maimonides' legal thought to the Talmud; his doctrine of a just war; and his theory of redemption and Messianism. The history section examines Maimonides' accession to the position of head of the Jewish community in its historical context, at the time of the rise of the Ayyubid dynasty under Saladin.